2012
DOI: 10.1161/atvbaha.112.254011
|View full text |Cite|
|
Sign up to set email alerts
|

P300/CBP Associated Factor Regulates Nitroglycerin-Dependent Arterial Relaxation by N ε -Lysine Acetylation of Contractile Proteins

Abstract: Objective-To address the role of epigenetic enzymes in the process of arterial vasorelaxation and nitrate tolerance, in vitro and in vivo experiments were performed in the presence or absence of glyceryl trinitrate (GTN) or histone deacetylases/ histone acetylases modulators. Methods and Results-In vitro single GTN administration rapidly increased cGMP synthesis and protein N ε -lysine acetylation in rat smooth muscle cells, including myosin light chain and smooth muscle actin. This phenomenon determined a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Prior observations indicated that the HAT activator SPV106 was proficient at promoting histone acetylation in normal and physiopathological conditions (23,28,29). In this study, we wished to investigate whether D-CMSC could be sensitive to the increase of histone acetylation levels.…”
Section: Discussionmentioning
confidence: 99%
“…Prior observations indicated that the HAT activator SPV106 was proficient at promoting histone acetylation in normal and physiopathological conditions (23,28,29). In this study, we wished to investigate whether D-CMSC could be sensitive to the increase of histone acetylation levels.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the silencing of polycomb or the activation of HDACs and SIRTs have been reported during the various phases of skin repair but their role in the regulation of these processes is yet poorly characterized (25,26). Intriguingly, NO has been found functionally relevant in all phases of WH and recent observations have shown that it modulates gene expression by regulating the function of epigenetic enzymes such as histone acetylases and deacetylases (4,27). Noteworthy, members of the class-III HDACs, the sirtuins, have been described to modulate eNOS function eliciting a significant increase in NO production by a lysine deacetylation-dependent process (8).…”
Section: Discussionmentioning
confidence: 99%
“…drugs that act on the acetylation levels of histones, thereby modifying DNA expression), prevent tolerance in a murine model. 18 The possible clinical applications of this observation remain to be explored.…”
Section: Nitrate Tolerance and Intermittent Therapy: The Problem Remainsmentioning
confidence: 99%
“…by modulating the processes, for instance histone acetylation and deacetylation, which control which and how much genes are expressed). 18 Although research on the role of epigenetic regulation in cardiovascular pathophysiology is at its very beginning, it has been shown that the so-called 'epi-drugs' (i.e. drugs that act on the acetylation levels of histones, thereby modifying DNA expression), prevent tolerance in a murine model.…”
Section: Nitrate Tolerance and Intermittent Therapy: The Problem Remainsmentioning
confidence: 99%